THE INFLUENCE OF PHONOLOGY ON SECOND LANGUAGE ACQUISITION - Yani Lubis; Sabilla Ayu Andini; Puput Handriani; Nazeeva Yusrina (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This research examines the role of phonology in the process of second language acquisition. Phonology, as a branch of linguistics that studies the sound system of a language, has a significant impact on a learner's ability to master the target language. This study aims to analyze how the differences in the phonological system between the mother tongue and the second language affect the ability of learners to perceive and produce language sounds. The methods used include a comprehensive literature review and case studies of English as a second language learners from various mother tongue backgrounds. The research results show that phonological transfer from the mother tongue to the second language can cause difficulties in pronunciation and comprehension. However, good phonological awareness and appropriate training can help overcome these obstacles. These findings have important implications for second language teaching, emphasizing the importance of focusing on phonological aspects in curriculum and teaching methods. Further research is needed to develop effective strategies for overcoming phonological challenges in second language acquisition.